COUNTER-DISCOURSE AND POWER IN AHMED YERIMAH’S HARD GROUND AND UWEMEDIMO ATAKPO’S WATERING THE HARD GROUND - Udofia, Anietie Francis (UI Scholars Hub, 2024)
Niger Delta uprising always evokes controversial positions viewed from a single perspective from the pages of print to electronic media with which many dramas and films on their themes clone some intertextual discourses as the absolute voice on the Niger Deltans’ problem. The major concern is usually the violence caused by the people of the Niger Delta to disrupt the peace of the Nigerian society without giving a second thought to the people’s complaint about the political which worsens the situations of the region. Using qualitative research methodology, framed on Mikhail Bakhtins’ theory of Dialogism as a suitable theoretical framework for essential critical guide, this paper discusses Uwemedimo Atakpo’s Watering the Hard Ground as a counter-discourse to Ahmed Yerima’s position in Hard Ground over Niger Delta people’s struggle, activities and their way forward in Nigeria. The objectives of the study are to examine the positions raised in Hard Ground and the counter point in Hard Ground on Niger Delta situation; to identify the areas of convergences and divergences in the two texts, and to assess how each text negotiates the way forward for the region. Findings show that Hard Ground discusses aggressiveness and self-destruction as the cause of frustration, while Watering the Hard Ground negotiates neglect and exclusion from the mainstream of lucrative activities as the cause of aggressiveness in Niger Delta. The two texts agree that violence is destructive to both the Government and the people; Hard Ground suggests repentance as a solution, while Watering the Hard Ground suggests the cleansing off of the industrial pollutions, education and inclusion of the people in government benefits. The paper concludes that dialogue between the two texts has given rise to a rational rethink over the Niger Delta controversy, and that counter-discourse may raise inimical frontiers in drama but it evolves a fresh premise that generates power to the society.